Information Provision for Monitoring the Sustainable Development of the Land and Biodiversity - Chala, Tetyana; Korepanov, Oleksiy; Lazebnyk, Iuliia; Chernenko, Daryna; Korepanov, Georgii; Чала, Тетяна Георгіївна; Корепанов, Олексій Сергійович; Лазебник, Юлія Олександрівна; Корепанов, Георгій Сергійович (Kryvyi Rih : IOP Publishing, 2023)
The study is focused on gathering information to monitor sustainable land development and biodiversity. The article discusses the objectives and measures required to achieve Sustainable Development Goal 15 "Protect, restore and promote sustainable use of terrestrial ecosystems, sustainably manage forests, combat desertifcation, and halt and reverse land degradation and halt biodiversity loss". This paper shows the results of the analysis of key indicators and values for Ukraine. It also contains the developed conceptual diagram for managing the sustainable development of ecosystems and biodiversity. There were identifed the main sources of statistical information, including traditional enterprise-level data and big data, and analyzed changes in indicators for monitoring the achievement of the Sustainable Development Goals at micro level under section "Environmental area". The study also identifed potential sources of information for calculating the presented indicators and explored the use of big data to develop an information base for monitoring, evaluating, and policy development related to sustainable land development and biodiversity. Further research and studies are needed to determine the algorithms of data processing, modelling and constructing of integrated indicators.

Дослідження зосереджено на зборі інформації для моніторингу сталого розвитку земель та біорізноманіття. У статті розглядаються цілі та заходи, необхідні для досягнення Цілі сталого розвитку 15 «Захищати, відновлювати та сприяти сталому використанню наземних екосистем, стале управління лісами, боротьба з опустелюванням, зупинити та повернути назад деградацію земель і зупинити втрату біорізноманіття». У цій статті представлено результати аналізу ключових показників та значень для України. Вона також містить розроблену концептуальну схему управління сталим розвитком екосистем та біорізноманіттям. Були визначені основні джерела статистичної інформації, включаючи традиційні дані на рівні підприємств та великі дані, а також проаналізовані зміни показників для моніторингу досягнення Цілей сталого розвитку на мікрорівні в розділі «Довкілля». У дослідженні також визначено потенційні джерела інформації для розрахунку представлених показників та досліджено використання великих даних для розробки інформаційної бази для моніторингу, оцінки та розробки політики, пов'язаної зі сталим розвитком земель та біорізноманіттям. Необхідні подальші дослідження та дослідження для визначення алгоритмів обробки даних, моделювання та побудови інтегрованих показників.
Інформаційне забезпечення для моніторингу сталого розвитку земель та біорізноманіття
Keywords: SOCIAL SCIENCES::Business and economics::Economics; SOCIAL SCIENCES::Statistics, computer and systems science::Statistics; sustainable development; сталий розвиток; land and biodiversity; земля та біорізноманіття; information provision; інформаційне забезпечення; monitoring; моніторинг